Effectiveness of Giving Warm Compress to the Abdomen Wall Area and Major Vein Area on Reducing Body Temperature - Setiawan, Mohammad Dwi Puspa; Kurniawan, Mohammad Setya Puspa; Veronita, Ika (Indonesian Journal of Nursing and Health Sciences, 2025)
Fever is a common clinical condition in pediatric patients and requires appropriate management to ensure comfort and prevent complications. Warm compress therapy is a non-pharmacological nursing intervention that supports thermoregulation by promoting peripheral vasodilation and enhancing heat dissipation. This study reviews the physiological basis, clinical application, and effectiveness of warm compresses in reducing fever among children. Evidence from previous studies indicates that warm compress therapy can moderately reduce body temperature, increase patient comfort, and decrease reliance on antipyretic medications. Data collection followed several preparatory steps, including a preliminary survey, development of measurement instruments, submission of the research proposal, and obtaining ethical and institutional approval. During data collection, researchers ensured that all participants received standardized instructions and identical warm compress procedures to maintain intervention consistency. The study generated interval-scale body temperature data, which were analyzed using both univariate and bivariate statistical methods. The findings highlight the importance of integrating warm compresses into routine pediatric nursing care as a safe and accessible intervention that strengthens non-pharmacological fever management strategies.